2013
DOI: 10.1093/nar/gkt835
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 dependent recruitment of the amyotrophic lateral sclerosis-associated protein FUS/TLS to sites of oxidative DNA damage

Abstract: Amyotrophic lateral sclerosis (ALS) is associated with progressive degeneration of motor neurons. Several of the genes associated with this disease encode proteins involved in RNA processing, including fused-in-sarcoma/translocated-in-sarcoma (FUS/TLS). FUS is a member of the heterogeneous nuclear ribonucleoprotein (hnRNP) family of proteins that bind thousands of pre-mRNAs and can regulate their splicing. Here, we have examined the possibility that FUS is also a component of the cellular response to DNA damag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
146
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(160 citation statements)
references
References 46 publications
13
146
1
Order By: Relevance
“…Based on the results described here and the work of others, there is already support for this view of ALS pathogenesis, especially with respect to FUS-related cases. Our results fit with earlier observations showing that FUS localizes to sites of UV-laser induced DSBs and supporting a role for FUS in DNA repair (6,7,19).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Based on the results described here and the work of others, there is already support for this view of ALS pathogenesis, especially with respect to FUS-related cases. Our results fit with earlier observations showing that FUS localizes to sites of UV-laser induced DSBs and supporting a role for FUS in DNA repair (6,7,19).…”
Section: Discussionsupporting
confidence: 92%
“…The finding that FUS participates in the prevention or repair of transcription-associated DNA damage is consistent with the prior finding that FUS localizes to DSBs induced by a UV laser (6,7,19). The latter observation suggests two functional possibilities: (i) that FUS participates in the repair of DSBs, per se, and (ii) that it localizes to breaks located near sites of transcription-associated DNA damage.…”
Section: Depletion Of Fus and Tdp43 Leads To Excessive Transcription supporting
confidence: 89%
“…FUS has also previously been implicated in DNA repair (Rulten et al, 2014;Wang et al, 2013). Indeed, we found that FUS accumulated at DNA lesions within a second of laser-mediated irradiation (Figures 1D, S1C, and S1D; Movie S1).…”
Section: Resultssupporting
confidence: 58%
“…The Prion-like Protein FUS Assembles into Various Dynamic Compartments In Vivo Previous reports have implicated FUS in the formation of stressinducible compartments, such as DNA damage sites and stress granules Mastrocola et al, 2013;Rulten et al, 2014;Wang et al, 2013). These studies often used transient transfection protocols and overexpression plasmids to study the subcellular localization of FUS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation